Accuracy and validity of sentinel lymph node biopsy for breast cancer using a photosensitizer: 8‐year follow‐up. Issue 9 (30th September 2013) - Yamada, Kimito; Ogata, Akihiko; Kaise, Hiroshi; Oda, Miki; Kimura, Fuyou; Komatsu, Seiichirou; Nakamura, Yukiko; Hosonaga, Mari; Matsumura, Mayuko; Kawate, Takahiko; Miyahara, Kana; Kawai, Yuko; et al.
Abstract Background and Objective We evaluated an alternative procedure for sentinel lymph node biopsy (SLNB) for breast cancer after approval of the study by the Ethics Committee of Tokyo Medical University Hospital in 2004. We examined the efficacy and safety of SLNB using the photosensitizer talaporfin sodium (Laserphyrin®, Meiji Seika Pharma, Tokoyo, Japan), compared with current methods. Study Design/Patients and Methods The study included 21 breast cancer patients (Japanese women; median age, 54 years; range, 35–75). All patients received a breast cancer operation combined with SLNB between June 2004 and May 2005. Three milliliters of talaporfin solution was locally injected into the subareolar region just before the operation. We attempted to identify a sentinel lymph node (SLN) that exhibited fluorescence and was consistent with a radioisotope (RI) localization technique. Our purpose was to verify the accuracy and validity of the talaporfin fluorescence imaging method after 8 years of application. Results There was no consistent correlation between fluorescence and pathological SLN metastasis, although all four cases of pathological SLN metastasis revealed positive fluorescence. In some cases in which we could not identify SLNs by the RI technique, we could identify SLNs using talaporfin. The method using talaporfin did not adversely affect the patients after the operation, even the chronic renal failure patient. After 8 years, all patients are alive, and none had lymph node recurrence. Side effects were not observed. Conclusion SLNB using the photosensitizer talaporfin sodium in breast cancer patients is considered to be useful as complementary to other current methods. We could evaluate the accuracy and validity of this method 8 years after all of the procedures were performed. In the future, a large‐scale clinical study with statistical analyses should be conducted. Lasers Surg. Med. 45:558–563, 2013. © 2013 Wiley Periodicals, Inc.